Investor Reactions to Russia-Ukraine War Years 2022 Using a Bayesian Analysis Approach - Morozov, Dmitry Alekseyevich Morozov; Takaliuang, Noldy; Hasanah, Yulia Nur Hasanah (ICON Publisher, 2025)
The purpose of this study was to determine the market reaction to changes in stock prices on the Russian-Ukraine war event on the Indonesia Stock Exchange in 2022. This research using Bayesian analysis Approach on banking stocks. The results show that the AAR and CAR Before-After of the three models do not show significant results or market anomaly. The implications of the results of this research for investors and researchers that the events of the Russian-Ukraine war in 2022 can be taken into consideration for investors to be more rational in responding to political events in making investments in both the financial sector or other sectors, and for other researchers the EMH theory is no longer relevant to recent world developments. The limitations in this study are only in the financial sector in banking stocks, and the future big agenda will be expanded in several sectors, namely manufacturing, infrastructure and technology on the Indonesia stock exchange. The novelty in this research is that it uses the Bayesian analysis approach to the three models of approaches that have been and are often used, but in this case it is very different from previous researchers who have never used the Bayesian analysis approach